Antimicrobial and antifungal activity of some (5-(adamantane-1-yl)-4R-1,2,4-triazole-3-ylthiols substitutes - V. M. Odyntsova (Zaporozhye State Medical University, 2016)
Lately adamantine containing substances have found wide use among the skeleton derivatives. The combination of adamantane and 1,2,4-triazole in one molecule creates significant preconditions to design new potential drugs with low toxicity and pronounced pharmacological activity. The aim of the research is the study of antimicrobial and antifungal activity of (5-(adamantane-1-yl)-4-R-1,2,4-triazole-3-ylthiols substitutes. Materials and methods. Determination of antimicrobial and antifungal activity has been carried out by 2-fold serial dilutions method in liquid nutrient media. The substance of the antibacterial drug Trimethoprim has been applied as a control in determining antimicrobial activity of the compounds against the investigated strains of microorganisms. Results. According to the data of experiments the 5-(((5-(adamantane-1-yl)-4-ethyl-4H-1,2,4-triazole-3-yl)thio)methyl)-4-ethyl-4H-1,2,4-triazole-3-thiol shows the same activity as Trimethoprim against P. aeruginosa (MIC is 62.5 µg/ml, MBC - 125 μg/ml), marked activity towards S. aureus (MIC is 15.6 μg/ml, MBC - 31.25 μg/ml while trimethoprim - 31.25 μg/ml, MBC - 62.5 µg/ml), greater fungistatic and fungicidal activity towards C. albicans, which amounted to 31.25 µg/ml, MFC - 62.5 µg/ml (while trimethoprim 62.5 µg/ml, MFC - 125 µg/ml). Reconstration of benzyldenhydrazide group to hydrazide one leads to the slight increase of bacteriostatic activity. Replacing the radical R from -Н to -C2H5 does not influence on the change of fungistatic activity. However, this resulted to the decrease in bacteriostatic activity against E. coli. The same is observed in relation to P. aeruginosa: from 62.5 μg/ml, MFC - 125 mcg/ml to 125 μg/ml, MFC - 125 µg/m respectively. Conclusion. The conducted study has showed that among the synthesized compounds there are some substances which strength of the antimicrobial and antifungal action in some cases exceeds the standard of comparison - Trimethoprim. The most active compound against the test strain of C. albicans was 2-(5-(((5-(adamantane-1-yl)-4H-1,2,4-triazole-3-yl)thio)methyl)-1,3,4-thiodiazole(todosol)-2-amine), which activity in 8 times higher than the standard of comparison. The study of biological and pharmacological activity of the synthesized compounds, and also the determination of the regularities between structure and activity create a favorable basis for the search of new medicines in a number of 1,2,4-triazole derivatives.